PHARMACOKINETICS INTERACTION STUDY OF METFORMIN AND METHYLDOPA IN TYPE II DIABETIC PATIENTS WITH HYPERTENSION. - Bello, S. S; Sani, F. B; Odunola, M. T; Garba, M.; Garba, M. A (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2017)
Pharmaceutical drug interaction may result in the alterations of the absorption, distribution, metabolism and excretion of a drug and this may affect its pharmaceutical actions. Diabetes and high blood pressure tend to occur together because they share certain physiological traits. Metformin is widely used in Nigeria to manage type II diabetes in hypertensive patients. Metformin (1 g) was administered alone and with 250 mg of Methyldopa to patients diagnosed for diabetes with hypertension. HPLC method (Agilent Technologies, 1120 LC series, USA) was used to analysed the serum samples of the patients using Hypersil C18 column at a wavelength of 238 nm. Solvent system was acetonitrile with methanol and buffer (13:7:80). The maximum concentration of Metformin insignificantly decreased from Cmax 1890±0.22 ng/ml to 1752.17±0.5 ng/ml when alone and when co-administered with Methyldopa at maximum absorption time of 3 hrs. Area under curve (AUC) 0-8h also insignificantly increased from AUC0-8 8882.10 ng/ml/h to 8895.30 ng/ml/h metformin alone and when interacted with methyldopa. AUC 0-∞ also decreased from AUC 0-∞ 12106.87ng.h/ml metformin alone to AUC0-∞ 12061.80 ng .h/ml when interacted with Methyldopa. Elimination rate constant, Kel, decreased from Kel, 0.116h-1 for metformin alone to 0.105 h-1 when interacted with Methyldopa. This result show the significant increase observed in the elimination half-life when Methyldopa was co- administered with metformin. This has also increased clearance (Cl) of the drugs, though, clinically insignificant. Administration of metformin with Methyldopa was clinically acceptable for therapeutic management of Type 2 Diabetic with Hypertension.